Acoustic CR Neuromodulation Therapy for Subjective Tonal Tinnitus: A Review of Clinical Outcomes in an Independent Audiology Practice Setting - Williams, Mark; Hauptmann, Christian; Patel, Nitesh (Frontiers in Neurology, 2015)
OBJECTIVE: To describe the quantitative treatment outcomes of patients undergoing acoustic coordinated reset (CR) neuromodulation at a single independent audiology practice over a 22 – 26 week period as part of an open label, non-randomized, non-controlled observational study. Methods: Sixty six patients with subjective tonal tinnitus were treated with acoustic CR Neuromodulation with a retrospective review of patient records being performed in order to identify changes of visual analogue scale (VAS, n=66) and in the score of the Tinnitus Handicap Questionnaire (THQ, n =51). Patients had their tinnitus severity recorded prior to the initiation of therapy using the Tinnitus Handicap Inventory (THI) in order to categorize patients into slight up to catastrophic impact categories. THQ and VAS for tinnitus loudness / annoyance were obtained at the patient’s initial visit, at 10-14 weeks and 22-26 weeks. RESULTS: VAS scores were significantly improved, demonstrating a 25.8% mean reduction in tinnitus loudness and a 32% mean reduction in tinnitus annoyance with a clinically significant reduction in percept loudness and annoyance being recorded in 59.1% and 72.7% of the patient group. THQ scores were significantly improved by 19.4% after 22-26 weeks of therapy compared to baseline. CONCLUSION: Acoustic CR neuromodulation therapy appears to be a practical and promising treatment for subjective tonal tinnitus. However, due to the lack of a control group it is difficult to reach an absolute conclusion regarding to what extent the observed effects are related directly to the acoustic CR neuromodulation therapy. Also as the observed patient group was made up of paying clients it is unknown as to whether this could have caused any additional placebo like effects to influence the final results.